Fasts and Feasts in Estonians’ Representations of the Seto Culture - Andreas Kalkun (Journal of Ethnology and Folkloristics)
Descriptions of Seto culture written at the end of the 19th and beginning of the 20th centuries mentioned both exhausting Orthodox fasts and heavy drinking on church calendar holidays remarkably often. The incorporation of the Seto areas into the Republic of Estonia, established in 1918, soon revealed some conflict due to cultural differences. The religious rituals of the Seto came to be regarded with a fresh eye: traditional fasting was associated with the discourse of health care, food sacrifice with economy and religious feasts with criminal activities and alcoholism. Estonians measured the economic profit and loss of religious practices and their effects on health, but failed to understand that for the religious Seto, the observance of traditional ritual practices was the only possible conduct, and such practical considerations were irrelevant. Fasts and feasts were stigmatised in both popular and academic representations of Seto culture. Seto religious piety and feasts were regarded in the young Republic of Estonia as an attack on a common national identity, something that subverted the ideals of abstemious and secular nationalism.